Post a New Question

Algebra 1

posted by .

Using substitution, solve this equation..
3x - 5y = 11
x - 3y = 1

  • Algebra 1 -

    Equation 2 looks like it would be easy to solve for x, so we take it and isolate x:


    x - 3y = 1

    x = 1 + 3 y


    Now we can use this result and substitute x = 1 + 3 y in for x in equation 1:


    3x - 5y = 11

    3 * ( 1 + 3 y ) - 5 y = 11

    3 + 9 y - 5 y = 11

    3 + 4 y = 11

    4 y = 11 - 3

    4 y = 8 Divide both sides with 4

    y = 2



    x = 1 + 3 y

    x = 1 + 3 * 2

    x = 1 + 6

    x = 7

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question